The Relationship Between Knowledge and Attitude of Families Caring for Dementia Patients at Home and the Frequency of Readmissions - Putri Suci Kristanti; Handayani Handayani; Sari Narulita; Rina Sogirin (Indonesian Journal of Global Health Research, 2026)
Dementia in elderly patients presents significant challenges for both individuals and their families, often leading to frequent hospital readmissions. Family caregivers play a critical role in patient management, and their knowledge and attitudes toward dementia care may influence patient outcomes. This study aimed to examine the relationship between family knowledge in caring for dementia patients and the frequency of hospital readmissions at RS Soeharto Heerdjan, Jakarta. A quantitative cross-sectional design was employed, with a total sampling method involving family members of dementia patients visiting the Psychogeriatric Outpatient Clinic and the Inpatient Geriatric Ward. Data were collected using the Indonesian versions of the Dementia Knowledge Assessment Scale (DKAS) and Dementia Attitudes Scale (DAS), both validated for reliability. The DKAS (Dementia Knowledge Assessment Scale) instrument is a measurement tool for assessing general knowledge about dementia. The latest version of DKAS has 25 items that include statements about dementia that can be judged as true or false, some of which are false statements and are judged in reverse. The Dementia Attitudes Scale (DAS) instrument is a measurement tool developed to measure a person's attitude towards dementia, covering affective (feeling), behavioural, and cognitive components related to people with dementia. The watershed consists of 20 items that show two main factors, namely knowledge of dementia and social comfort in interacting with people with dementia. Results indicated that 52.5% of respondents had low knowledge and 50.8% held negative attitudes toward dementia care. High patient readmission frequency (>1 time per year) was reported in 83.6% of cases. Statistical analysis using Pearson Chi-Square (p = 0.865), Fisher Exact (p = 1.000), and odds ratio (OR = 0.889) showed no significant association between family knowledge and readmission frequency, although a slight trend suggested that higher knowledge may reduce readmissions. Despite the lack of statistical significance, these findings highlight the importance of educating and supporting family caregivers to improve patient care and quality of life, potentially minimizing hospital readmissions. Interventions targeting caregiver knowledge and attitudes are recommended to enhance dementia management and reduce healthcare burden.